Perlindungan Hukum Terhadap Pembeli Beritikad Baik Atas Tanah yang Belum Dibaliknamakan (Studi Putusan Pengadilan Negeri Nomor 389/Pdt.G/2023/Pn Bks) - Yudhistira, Ferdian; Nasution, Krisnadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In practice, the transfer of land rights is often conducted without fulfilling formal registration procedures, particularly without the issuance of a deed by the Land Deed Official, resulting in good faith purchasers being unable to register the transfer of title and facing legal uncertainty despite having fulfilled their contractual obligations. This study aims to analyze the form of legal protection afforded to good faith purchasers of land whose ownership rights have not yet been formally transferred, as well as the legal considerations of the panel of judges in the Decision of the Bekasi District Court Number 389/Pdt.G/2023/PN Bks. This research employs a normative legal research method using statutory and case approaches. The results indicate that legal protection is provided through recognition of the material validity of the land sale agreement despite the absence of formal requirements, as well as through a court decision granting authority to the purchaser to process the transfer of land title. The judges’ considerations are based on the fulfillment of the legal requirements of a valid agreement under Article 1320 of the Indonesian Civil Code, the seller’s breach of contract, the purchaser’s physical possession of the land, and the application of the principles of good faith and substantive justice to ensure legal certainty.